PTOLEMEOS: Α 4π γ-detection system for Nuclear Astrophysics - Harissopulos, S.; Kossionides, S.; Galios, G.; Paradellis, T. (HNPS Advances in Nuclear Physics, 2020)
A new 4π detector system, called PTOLEMEOS, especially designed for the study of (p,γ) and (α,γ) reactions of astrophysical interest is presented. Technical data of the target system designed for PTOLEMEOS are also given.